PENDEKATAN KEMANUSIAAN DALAM PEMBERDAYAAN KOMUNITAS ADAT TERPENCIL DI DAERAH PERBATASAN Kasus di Kalimantan Barat dan Nusa Tenggara Timur - Bambang Rustanto (Politeknik Kesejahteraan Sosial, 2007)
Our country is bordered with many other countries, such as sea border and also mainlandborder. Having two territories which extremely dangerous toward security disturbed alsosocial-economy and culture, that is West Kalimantan and East Nusa Tenggara. People who stay in that border, in general are the indigenous people which need attention in order to increase their social welfare. Humanistic approach must first priority compare with militaristic-repressive approach because they are as a border guard of our country.Key Words : humanistic approach, militaristic-repressive approach